2012
DOI: 10.4103/0975-7406.100206
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of Streptococcus mutans and Candida albicans to different bracket materials

Abstract: Objective:To quantify the adherence of Streptococcus mutans and Candida albicans on brackets made of stainless steel, plastic, ceramic, titanium, and gold, and to evaluate the various sites of adherence of these microorganisms with scanning electron microscopy (SEM).Materials and Methods:Brackets made of stainless steel, plastic, ceramic, titanium, and gold were used. The adherence of S. mutans and C. albicans were studied. The brackets were placed in flat-bottomed vials containing basal medium with 20% sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Dual species interaction of C. albicans and S. mutans is found in the ECC (Marchant et al, 2001;de Carvalho et al, 2006;Raja et al, 2010) and in bracket materials (Rammohan et al, 2012). Also, S. mutans and C. albicans have been found together in carious lesions (Vílchez et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…Dual species interaction of C. albicans and S. mutans is found in the ECC (Marchant et al, 2001;de Carvalho et al, 2006;Raja et al, 2010) and in bracket materials (Rammohan et al, 2012). Also, S. mutans and C. albicans have been found together in carious lesions (Vílchez et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…The study also observed that a longer incubation time significantly increased the adhesion of cariogenic streptococci, irrespective of the strain, the type of bracket, and saliva coating and the amount of adhesion was highest in the sample incubated for 6 hours [11]. Moreover, the adherence of S. mutans and C. albicans varied according to the bracket materials, with ceramic having the greatest and stainless steel having the least adherence [12]. Long-term biofilm formation on metal and ceramic brackets showed that ceramic brackets exhibit less longterm biofilm accumulation than metal brackets [13].…”
Section: Discussionmentioning
confidence: 73%
“…Researchers like Shrinivaasan Nambi Rammohan, Ahn, Papaioannou, Fournier, or Brusca explored the relationship between CFUs (S. mutans alone, C. albicans alone, S. mutans, and C. albicans in combination) on surfaces of different kinds of orthodontic materials. When S. mutans was evaluated alone Shrinivaasan et al [104], Papaioannou et al [105], Fournier et al [106], and Brusca et al [107] found no obvious difference in the adhesion of S. mutans to stainless steel, plastic, and ceramic brackets. Quite different results were obtained Ahn et al [108] There was a greater number of CFUs on stainless steel brackets than on plastic and ceramic brackets.…”
Section: Introduction Of Nanofillers or Np (Silver Tio 2 ) To Orthodontic Adhesivesmentioning
confidence: 99%